Survival outcome of adjuvant radiotherapy after local excision for T2 early rectal cancer: An analysis based on the surveillance, epidemiology, and end result registry database. Issue 12 (December 2018) - Wang, Xiao-Jie; Chi, Pan; Zhang, Yue-Yi; Lin, Hui-Ming; Lu, Xing-Rong; Huang, Ying; Xu, Zong-Bin; Ghareeb, Waleed M.; Huang, Sheng-Hui; Sun, Yan-Wu; Ye, Dao-Xiong
Abstract: Background: Major resection (MR) is recommended for cases with T2 finding after local excision (LE) of early rectal cancer, but the revision procedure is accompanied with high morbidity. We evaluated the oncological safety of LE followed by adjuvant radiotherapy as a rectum-preserving alternative to MR for T2 early rectal cancer. Methods: A total of 3786 patients with T2N0M0 rectal adenocarcinoma between 1998 and 2013 were included from the SEER database. Survival rates were compared using the Kaplan-Meier method with a log-rank test, and multivariate analyses were performed using Cox proportional regression models. Results: Of these patients included, 429 (11.3%) treated with LE alone (LE group), 3067 (81.0%) treated with MR (MR group), and 290 (7.7%) treated with LE followed by adjuvant radiotherapy (LE + adjuvant RT group). The 5-year cancer specific survival (CSS) rate and 5-year overall survival (OS) rate were significantly lower in LE patients group than those in MR patients group (70.5% vs. 81.8%, P < 0.001; 57.3% vs. 72.3%, P < 0.001). The 5-year CSS rate and 5-year OS rate were similar between LE + adjuvant RT and MR groups (78.4% vs. 81.8%, P = 0.975, and 70.7% vs. 72.3%, P = 0.311, respectively). Multivariate Cox regression revealed that treatment strategies, age and CEA status were independently associated with CSS and OS. After age adjustment, LE was associated with reduced CSS (using MR as a reference, HR, 1.784; P < 0.001) and reduced OS (HR, 1.739; P < 0.001). However, CSS and OS related to LE + adjuvant RT of T2 rectal cancer group weren't be affected (HR, 0.994; P = 0.962 and HR, 0.904; P = 0.302, respectively). Conclusions: When MR is inappropriate for T2 early rectal cancer patients because of patients refusal or co-morbidities, LE + adjuvant RT can provide acceptable levels of long-term survival.